2021
DOI: 10.1155/2021/2259093
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Oral Microbiota in Patients with Esophageal Cancer in China

Abstract: Gut microbiota dysbiosis is closely associated with intestinal carcinogenesis, but the oral microbiota of patients with esophageal squamous cell carcinoma who live in high-risk regions in China has not been fully characterized. In the current study, oral microbial diversity was investigated in 33 patients with esophageal squamous cell carcinoma and 35 healthy controls in Chongqing, China, by sequencing 16S rRNA of V3-V4 gene regions. There were statistically significant differences in oral microbiota between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This systematic review obtained 19 studies examining the oral microbiota in oral cancer. The studies were conducted in 10 Asian countries, 8,[18][19][20][21][22][23][24][25] two studies in Australia, 14,26 and six studies in United States of America (USA), 9,[27][28][29] and two studies in Europe. 30,31 The types of studies used were cohort (n=6) and cross-sectional (n=14).…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review obtained 19 studies examining the oral microbiota in oral cancer. The studies were conducted in 10 Asian countries, 8,[18][19][20][21][22][23][24][25] two studies in Australia, 14,26 and six studies in United States of America (USA), 9,[27][28][29] and two studies in Europe. 30,31 The types of studies used were cohort (n=6) and cross-sectional (n=14).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we found that Firmicutes and Streptococcus were significantly increased while Lactobacillales and Pasteurellaceae were significantly decreased in oral cavity of HIV patients with KSHV oral shedding. Additional studies demonstrated higher abundances of Streptococcus in the salivary microbiome of several oral cancers or head and neck cancers, including salivary adenoid cystic carcinoma (SACC), oral squamous cell carcinoma (OSCC), and esophageal squamous cell carcinoma (ESCC; Jiang et al, 2021 ; Li et al, 2021 ; Stasiewicz and Karpinski, 2021 ). Thus, these data indicate potential contribution of Streptococcus to different oral cancers development.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the effects of the above mentioned pathogens, other experiments showed different possibilities of the influence of the oral microbiota. A study on about oral microbiota in patients with esophageal cancer was conducted by Hezi Li et al (Li H et al, 2021). In this study, microbiota analysis was performed by sequencing the 16S rRNA of V3-V4 gene regions.…”
Section: Alterations In the Oral Microbiotamentioning
confidence: 99%
“…A study on about oral microbiota in patients with esophageal cancer was conducted by Hezi Li et al. ( Li H et al., 2021 ). In this study, microbiota analysis was performed by sequencing the 16S rRNA of V3-V4 gene regions.…”
Section: Alterations In the Oral Microbiotamentioning
confidence: 99%
See 1 more Smart Citation